2006
DOI: 10.1161/circulationaha.105.559724
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Histone Deacetylation Blocks Cardiac Hypertrophy Induced by Angiotensin II Infusion and Aortic Banding

Abstract: Background-A number of distinct stress signaling pathways in myocardium cause cardiac hypertrophy and heart failure.Class II histone deacetylases (HDACs) antagonize several stress-induced pathways and hypertrophy. However, cardiac hypertrophy induced by transgenic overexpression of the homeodomain only protein, HOP, can be prevented by the nonspecific HDAC inhibitors trichostatin A and valproic acid, suggesting that alternate targets that oppose class II HDAC function might exist in myocardium. We tested the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
260
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(281 citation statements)
references
References 30 publications
19
260
1
1
Order By: Relevance
“…Cardiac sections from infarcted hearts receiving siRNA HDAC4-treated c-kit ϩ CSCs did not demonstrate the formation of tumorigenesis in hearts 6 mo after cell engraftment (data not shown), suggesting that HDAC4 inhibition in c-kit ϩ CSCs does not increase the risk of developing teratomas. In addition, c-kit ϩ CSCs-engrafted MI hearts antagonized cardiac hypertrophy, which is in line with previous observations that inhibition of HDACs showed cardioprotection and blocks cardiac hypertrophy (22,23).…”
Section: Discussionsupporting
confidence: 90%
“…Cardiac sections from infarcted hearts receiving siRNA HDAC4-treated c-kit ϩ CSCs did not demonstrate the formation of tumorigenesis in hearts 6 mo after cell engraftment (data not shown), suggesting that HDAC4 inhibition in c-kit ϩ CSCs does not increase the risk of developing teratomas. In addition, c-kit ϩ CSCs-engrafted MI hearts antagonized cardiac hypertrophy, which is in line with previous observations that inhibition of HDACs showed cardioprotection and blocks cardiac hypertrophy (22,23).…”
Section: Discussionsupporting
confidence: 90%
“…CM Klf4 KO mice and control mice received a daily oral dose of olmesartan or a daily intraperitoneal injection of TSA during the continuous subcutaneous ISO infusion for 14 days. The doses and the routes of administration for these antihypertrophic reagents were as those employed in previous studies (16,18). Results showed that body weight, systolic blood pressure, and heart rate were unaltered by treatment with olmesartan or TSA, although the diastolic blood pressure was decreased by olmesartan treatment in ISO-untreated CM Klf4 KO mice and control mice (Fig.…”
Section: Klf4 Ko Mice Grewmentioning
confidence: 82%
“…Olmesartan (Daiichi-Sankyo Co. Ltd., Tokyo, Japan) was given by gavage at a dose of 10 mg/kg/day to a subset of mice for 14 days after the surgery (16,17). TSA (Sigma-Aldrich) at 0.6 mg/kg/day was injected intraperitoneally into a subset of mice for 14 days after the surgery (18). For the angiotensin II-induced cardiac hypertrophy model, mice received a subcutaneous infusion of angiotensin II (Sigma-Aldrich) at a rate of 2 mg/kg/day for 14 days, as described previously (19).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…60 Similarly, TSA and VPA suppressed LV hypertrophy induced by infusion of angiotensin II or pressure-overload due to transverse aortic constriction. 61 TSA treatment was also shown to regress established LV hypertrophy in mice subjected to aortic constriction, 61 and it reversed established atrial fibrosis in Hop-transgenic mice, 62 suggesting potential for HDAC inhibitors for the treatment of preexisting LV failure. Consistent with this, Hill and colleagues convincingly demonstrated that TSA reverses established LV hypertrophy in Beclin 1 transgenic mice subjected to pressure overload.…”
Section: Hdac Inhibitors In Models Of LV Failurementioning
confidence: 99%